A PROSPECTIVE RANDOMIZED OPEN-LABELED PARALLEL GROUP STUDY TO COMPARE THE EFFICACY OF ORAL TERBINAFINE VERSUS ORAL TERBINAFINE PLUS ORAL FLUCONAZOLE IN DERMATOPHYTE INFECTIONS - Shekhar, Amit; Mittal, Geetika; Chandane, Rakhamaji Dattarao; Suranagi, Umesh Devappa (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The objectives of this study were to assess the efficacy of oral monotherapy (Terbinafine) as compared to combination of oral drugs (Terbinafine and fluconazole) in treatment of dermatophyte infections. Methods: Patients of clinically diagnosed, potassium hydroxide (KOH) confirmed dermatophyte infections (n=235), were recruited as per inclusion criteria and randomized into Group A (Tab. Terbinafine 6 mg/kg body weight daily) and Group B (Tab. Terbinafine 6 mg/kg daily+Tab Fluconazole 3 mg/kg twice per week) treatment for 2 weeks. Assessment was done in beginning, after week 1 and after week 2 using visual analog scale (VAS) and global physician assessment (GPA). At the end of 4 weeks, they were again called back to assess the residual disease activity. Results: VAS scoring at week 1 and week 2 showed a significant reduction of scores in both the groups as compared to basal score of 0 week. Inter-group comparison showed decrease in mean-VAS itch scores in Group B as compared to Group A. Week 1 reduction in the Group B was statistically significant (p<0.001). GPA reflected a gradual but significant improvement in GPA scores end of week 1 and week 2 in both groups. The improvement seemed robust in Group B reflecting the stronger clinical response. The inter-group comparison showed statistically significant improvement in Group B over Group A in both 1stweek (p<0.001) and 2nd week (p=0.021). Conclusion: Dermatophyte infections treated with either terbinafine alone or terbinafine and fluconazole combination is clinically effective. Combination therapy is better than single drug therapy in terms of treatment response.